2022
DOI: 10.3390/bs12050135
|View full text |Cite
|
Sign up to set email alerts
|

English-Learning Motivation among Chinese Mature Learners: A Comparative Study of English and Non-English Majors

Abstract: This study examined the motivation of Chinese mature students toward learning English. The participants in the study were ten Chinese mature learners, of whom four were English majors and six were non-English majors. Each underwent a semi-structured interview. Their responses were then coded and analyzed based on Matsuzaka-Carreira’s motivation framework. Furthermore, the Keyword Extraction and Link Terms techniques of PolyAnalystTM were used for further analysis. The results showed that English majors tended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…Because English is a vitally important tool for English majors in their future career, they might be firstly motivated and try their best to learn, while for some non-English majors, they might not try to learn but directly display low self-efficacy or negative affects and eventually demotivation. Therefore, considering the differences of learning behaviors, requirements, foundations, goals, etc., among English and non-English majors (Sun et al, 2022), it could be better to differentiate the two groups of students when investigating college students' demotivation to learn English. Methodologically, although Ren and Abhakorn (2022) constructed a model, it was not tested among large college student sample, thus might not be appropriately be used to explain demotivation among large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Because English is a vitally important tool for English majors in their future career, they might be firstly motivated and try their best to learn, while for some non-English majors, they might not try to learn but directly display low self-efficacy or negative affects and eventually demotivation. Therefore, considering the differences of learning behaviors, requirements, foundations, goals, etc., among English and non-English majors (Sun et al, 2022), it could be better to differentiate the two groups of students when investigating college students' demotivation to learn English. Methodologically, although Ren and Abhakorn (2022) constructed a model, it was not tested among large college student sample, thus might not be appropriately be used to explain demotivation among large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…From the research results, it can be found that teachers improve flexibility to fully demonstrate various leadership styles, which will obviously help improve students' learning motivation [44]. When students set up their clear goal, teachers can also change to use the task-oriented leadership style to improve students' motivation [45]. However, for intelligence-related subjects-such as mathematics, etc.-in order to improve the intrinsic motivation of learning, it is necessary to demonstrate a support leadership style (support leadership).…”
Section: Hypothesis 8bmentioning
confidence: 99%
“…Consequently, these students have a personal stake in acquiring the language, which enhances their level of proficiency and fosters a more positive outlook on their learning outcomes compared to their counterparts who do not major in English. Over the past decade, several studies have examined the role of major in language learning motivation, yielding diverse results [27][28][29][30].…”
Section: Major and L2 Motivationmentioning
confidence: 99%